Superego in the Characters of P. Kemala’s Hampa Short Story - Nabila, Syarifah (Maliki Interdisciplinary Journal, 2025)
Research on psychoanalytic through superego in literary studies has yet to be done much by scientists. Short story that convey messages in the characterization cause researcher to examine psychoanalitic in the character’s personality. This study’s objectives were: 1) examining the types of superego in the characters traits, 2) analyzing how author constructs the dominan character, and 3) describing how to understand the purpose of psychoanalytic theory. The data was a all words, phrase, and sentences in the short story entitled “Hampa” by P. Kemala 2024. The data were analyzed using the superego types of psychoanalytic theory by Sigmund Freud (1923). The study’s results found that superego plays a role in the formation of a stable storyline. This research can also show how Character attitudes can affect social relationships between humans as well as an individual’s mental state. The superego character is created with the character’s attitude in dealing with conflicts that occur in life. In addition, Superego also provides an overview of the solution steps to solve a problem.